Changes in mechanical properties of minimally processed yellow pitahaya treated with 1-mcp (2012)
The mechanical properties stress of yield limit (σL), modulus of deformability (Ed), failure stress (σF), and Hencky strain at failure (εHF), of minimally-processed yellow pitahaya treated with 200 μgL-1 1-MCP during storage (10±1 °C, 85% RH) was evaluated. Mechanical analysis of the fruit was performed using a stress-strain curve. The samples were subjected to uniaxial compression test at break. The results showed that the samples treated with 1-MCP showed the highest values of stress of yield limit, modulus of deformability and failure stress. This indicates that the application of 1-MCP provides greater firmness to the fruit and may represent an alternative to reduce undesirable changes in texture during storage.